Setting the stage for corporate headquarters: A technological explanation for the rise of modern industrial corporations - Carliss Y. Baldwin (Journal of Organization Design, 2019)
This paper combines theories of organizational design with theories of production to provide a novel perspective, which helps explain the technological forces that led to the rise of vertically integrated "modern" corporations in the late nineteenth and early twentieth centuries. I describe the technology of a flow process with bottlenecks and show how this technology rewards unified governance, a hierarchical organization structure, and the use of direct authority. These properties in turn became the organizational hallmarks of "modern" industrial corporations with central corporate headquarters.
Keywords: 650